1998
DOI: 10.1016/s0014-5793(98)00631-0
|View full text |Cite
|
Sign up to set email alerts
|

β3‐Adrenergic relaxation of bovine iris sphincter

Abstract: Bovine iris sphincter in vitro responded to L Ladrenergic stimulation with pronounced relaxation (EC SH of isoproterenol = 0.3 nM), which was potentiated by the cAMP phosphodiesterase inhibitor, isobutylmethylxanthine, and mimicked by the adenylyl cyclase activator, forskolin. The L L I /L L P antagonist, propranolol, exhibited low potency with calculated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…IPB, a muscarinic blocker, was considered unanimously as the only cause of pupil dilation [2,7,10,11,14]. Our present findings confirm our previous report [5] and demonstrate that, at least in the bovine sphincter model, β-adrenergic agonists have a major relaxing effect on the basal tension of the iris sphincter and can counteract maximal contraction induced by muscarinic stimulus. Moreover, muscarinic blockade caused a major potentiation of β-adrenergically induced relaxation, in analogy to the synergism of the two drugs in clinical situations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IPB, a muscarinic blocker, was considered unanimously as the only cause of pupil dilation [2,7,10,11,14]. Our present findings confirm our previous report [5] and demonstrate that, at least in the bovine sphincter model, β-adrenergic agonists have a major relaxing effect on the basal tension of the iris sphincter and can counteract maximal contraction induced by muscarinic stimulus. Moreover, muscarinic blockade caused a major potentiation of β-adrenergically induced relaxation, in analogy to the synergism of the two drugs in clinical situations.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports from our own and other laboratories demonstrated that β-adrenergic agonists cause marked relaxation of isolated iris sphincter from many species, including bovine [5,12] and human [13]. These findings imply that, in addition to the proposed increase in aqueous humor production, the synergism of β-adrenergic stimulation and muscarinic inhibition may result from their combined effects on sphincter contractility.…”
Section: Introductionmentioning
confidence: 58%
“…It has previously been shown by others that stimulation of different iris b-receptors can cause a relaxation of the iris sphincter in various species (Patil 1969;Patil & Weber 1991;Geyer et al 1998;Toda et al 1999;Barilan et al 2003). Likewise, our group has previously demonstrated that epinine, a more unspecific adrenergic stimulator, has a mydriatic effect superseding that of phenylephrine (Lundberg & Behndig 2009).…”
Section: Discussionmentioning
confidence: 54%
“…Pharmacologically, phenylephrine ((R)-3-[-1-hydroxy-2-(methylamino)ethyl]phenol) is a specific a 1 -receptor agonist, and it is generally accepted that a 1 -receptors are the main mediators of the adrenergic mydriatic response of the iris dilator (Soldati et al 1993;Yu & Koss 2002. Mydriasis from an adrenergic substance, however, may also in part owe to stimulation of iris b-receptors, resulting in a relaxation of the pupil sphincter (Patil 1969;Yoshitomi et al 1988;Patil & Weber 1991;Geyer et al 1998;Toda et al 1999;Barilan et al 2003). This additional effect may explain why epinephrine ((R)-4-(1-hydroxy-2-(methylamino)ethyl)benzene-1,2-diol), a nonselective agonist of the adrenergic receptors (a 1 , a 2 , b 1 , b 2 and b 3 ), is a more potent mydriatic agent than phenylephrine when injected intracamerally in humans (Myers & Shugar 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The first support for a functional role of the β 3 -adrenoceptor in the eye has been delivered by Geyer and colleagues, who suggested that this receptor subtype contributes to β-adrenergic relaxation of the bovine iris sphincter possibly via an increase in cellular cyclic adenosine monophosphate (cAMP) concentration (Geyer et al 1998). The findings have been confirmed and extended by an independent study group reporting that β 2 -and β 3 -adrenoceptors mediate β-adrenergic relaxation responses in the bovine iris sphincter and ciliary muscle (Topalkara et al 2006).…”
mentioning
confidence: 99%